2012
DOI: 10.1177/0033688212463274
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback and Learner Uptake in a Child ESOL Classroom

Abstract: This study investigates the occurrence of corrective feedback and uptake in child ESOL classes. Transcripts of 8.1 hours of lessons in 6 ESOL classes in a New Zealand primary school were analysed to explore the relationship between errors, feedback, and uptake. The results revealed that there was a clear preference for recasts and explicit correction, and there was a lack of prompts. The two most frequent feedback types yielded relatively high uptake rates, which was ascribed to the fact that a high percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
53
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 26 publications
10
53
3
1
Order By: Relevance
“…The corrections made by the tutors revealed some interesting findings. As in other studies with students of different ages (Blake, 2000;Choi & Li, 2012;O'Rourke, 2005;Vinagre & Muñoz, 2011), the majority of the corrections in the current study were grammatical, followed by spelling and vocabulary. The lower frequency of feedback on vocabulary errors may be attributed to the greater possibility of inference provided by the writing medium, especially in asynchronous CMC where students have more time to read and understand the message.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The corrections made by the tutors revealed some interesting findings. As in other studies with students of different ages (Blake, 2000;Choi & Li, 2012;O'Rourke, 2005;Vinagre & Muñoz, 2011), the majority of the corrections in the current study were grammatical, followed by spelling and vocabulary. The lower frequency of feedback on vocabulary errors may be attributed to the greater possibility of inference provided by the writing medium, especially in asynchronous CMC where students have more time to read and understand the message.…”
Section: Discussionsupporting
confidence: 80%
“…More recently, the area of written feedback has received more attention with a typology proposed by Ellis (2009) and a number of studies in university settings (see Bitchener and Ferris, 2012 for a review). With a few exceptions (Choi & Li, 2012;Oliver, 1998) the studies have been carried out in adult university settings. According to Ferris (2010), there is now evidence that written corrective feedback provided under the right conditions facilitate L2 development and "help students improve the accuracy of their writing, at least for the particular features under consideration" (p. 186).…”
Section: Corrective Feedbackmentioning
confidence: 99%
“…All five activities were carried out in each lesson and repeated nine times with different sets of items. The teacher made every effort to provide corrective feedback when students chose the wrong card using recasts, as previous research has shown this to be the favoured corrective strategy for addressing errors in form‐focused instruction for young children (Choi & Li, ).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of different types of feedback can be understood from the evidence of learners' uptake and particularly when this move results in a successful repair (Tatawy, 2002). In this situation, learners' uptake would be taken as a proof of learners' observing their language errors (Choi & Li, 2012;Egi, 2010) as well as the "pushed output" concept given by Choi & Li, (2012). Furthermore, the researchers made it clear that learners' uptake provides evidence that they understood the teacher's strategy and that it helped them understand the gap between the form of target language and an interlanguage (Mackey & Oliver 2002;Sheen, 2004).…”
Section: Learners' Uptake or Self-repairmentioning
confidence: 99%